Personality Traits as Correlate of Adult Education Students’ Study Habits - Habibat Bolanle Abdulkareem; Abdulhafis Adeyinka Hassan; Abdullahi Suleiman (Indonesian Journal of Multidiciplinary Research, 2023)
The objectives of the study were to examine the profile of agreeableness of adult education students, the conscientiousness of adult education students, neuroticism of adult education students, openness to experience adult education students, extraversion of adult education students and the level of study habits of adult education students at the University of Ilorin. A descriptive research design of a survey was used for this study. The population of the study consist of all 567 undergraduate students of the adult education department at the University of Ilorin. A total sample of two hundred (200) respondents was selected using random sampling techniques. The structured questionnaire was validated by three experts at the Department of Adult and Primary education, University of Ilorin, Nigeria. Reliability validation was obtained through the split-half method with 70 respondents. The hypotheses were tested using Chi-square at 0.05 alpha level. It was concluded that the agreeableness, conscientiousness, extroversion and openness to experience of adult education students are high while their neuroticism was low. As a result, the majority of adult education students performed averagely in the study habit test, though agreeableness, conscientiousness, extroversion and openness as well as neuroticism are positively related to the study habits of adult education students at the University of Ilorin. However, adult education students’ conscientiousness, extroversion, agreeableness and openness to experience significantly predicted their study habits at the University of Ilorin while neuroticism was insignificant.